3D printable design of a compact spectrometer to analyse true colour - Mohamad Shalihin Ahmad (Nanyang Technological University, 2020)
Most commercial spectrometers are bulky, complicated to use, heavily dependent on power supply and rather expensive. With the ongoing list of emerging technologies in this new era, smartphones are becoming sophisticated, more advanced and are well capable of taking high quality images. Users of this portable spectrometer would be able to evaluate the spectrum received from a reflected object to obtain a defined true colour. The spectrophotometer measures the intensity of light relative to its wavelengths which allows light to be separated to its individual wavelength with the use of an optical grating. This separated light is called a spectrum. This would then enable users to evaluate the colours that appears on the object. Colours that appear naturally on object like bananas were used in the experiment to determine the capabilities of the spectrometer. In practice, the spectrometer was able to detect the colour differences between a green and a yellow banana. The results were analyzed using the spectrum image received from the wavelength of light that was reflected off the bananas. In contrast, a working portable smartphone spectrometer would be accessible for most people to use on a regular basis. Hence, this project aims to develop a 3D printed portable smartphone spectrometer.